Analisis Efektivitas Animasi Sebagai Media Promosi Kebudayaan China - Jimmy Pratama; Joyce Chrissy (Universitas Sarjanawiyata Tamansiswa, 2023)
Culture is people's reflection, hard work, and wisdom to navigate their world, namely a culture that allows people to see their environment in a meaningful way. Indonesia has diverse cultures, one of which is traditional Chinese culture. Over time, the Chinese culture in Indonesia has gradually faded to this day. This study aims to develop a 2D animated video to introduce Chinese tradition and culture as the identity of Chinese people in Indonesia, especially Gen Z children. Using a research and development approach and testing the EPIC model's effectiveness. The research conducted included interviews with several Mandarin teachers and students studying in China. The development phase uses the MDLC (Multimedia Development Life Cycle) model and continues with quantitative research using the EPIC model. These search results are 2D animated videos posted on YouTube that last 3 minutes and 35 seconds. The EPIC model's quantitative demonstrate how 2D animated videos effectively introduce culture to younger members of Generation Z. Empathy, persuasion, influence, and communication values all show this. The mean of the EPIC ratio is 4.16. The persuasion and communication dimension got the highest score compared to other dimensions at 4.26.